Effects of feeding free and protected acidulated oil on rumen fermentation and milk production in dairy cattle - Nurettin Gülşen; Fatma İnal; Behiç Coşkun; Cavit Arsian; H. Derya Umucalılar (Eurasian Journal of Veterinary Sciences)
In this study, the effects o! acidulated sunflower oil acidulated sunflower oil plus calcium and Ca soap which was prepared from acidulated sunflower oil on some rumen parameters, digestibility, milk production and milk production parameters in mid and late lactation periods of dairy cows were determined with two replicated 4x4 latin square design. Acidulated sunflower oil 8%, acidulated sunflower oil plus Ca and Ca soap was added 10% to concentrate diets In control group acidulated oil. acidulated oil plus Ca and Ca soap groups NH3*N levels were determined 125,5, 130.57, 120,05 and 129.98 mmol/l. total VFA values were 126.84, 138.35. 133.34 and 147.97 mmol/l tn the ruminal fluids respectively and among groups there was nol statistically significantly difference (P>0.05) Organic matter digestibility were lound 62.80, 58,49, 57.36 and 56.35%, crude fat digestibility was found 84,31. 85 81, 92.09 and 92.10% in groups respectively. Organic matter, crude fat crude protein and crude liber digestibilities were determined statistically non significant among groups (P>0,05) Diy matter intakes were determined 17.95 17.42 18.13 and 18.54 kg/day. milk productions were 23.34, 21.15. 19 1 and 21 73 kg'day. respectively.